Analisis Perilaku Politik Masyarakat Ras Minoritas Amerika Dalam Pemilihan Presiden Amerika 2020 - Hari Wangsa, Ni Nyoman Ritaro; Apriani, Kadek Dwita; Pramana, Gede Indra (Jurnal Nawala Politika, 2023)
This article stems from the author's interest in seeing how the political behaviour of minority communities in the United States is towards general elections, and how phenomena or issues that arise before the election influence their attitudes. This article also aims to determine the political behaviour of America's racial minority communities in the 2020 United States presidential election and find out the effect of racism on the participation and assessment of the black race in the 2020 United States presidential election. Conducting a literature study as an effort by the author to obtain data and analysis on political behaviour, there are several findings. First, the black community, in this case, the minority race, shows how race and community conditions in the field can influence how a figure is assessed. Second, racial factors can also influence people's participation in voicing their voices in general elections and this will also have a big influence on the final results of the vote count. Keywords: Racial Minorities, 2020 American Elections, Political Behavior.